Effects of hematocrit and red blood cell–independent viscosity on canine thromboelastographic tracings. Issue 3 (31st July 2013) - Brooks, Aimee C.; Guillaumin, Julien; Cooper, Edward S.; Couto, C. Guillermo
<x xml:space="preserve">Abstract</x> Background It is well established that hematocrit (Hct) influences whole blood thromboelastography (TEG) tracings. Previous studies showed hypercoagulable TEG tracings in anemic patients despite clinical expectations that anemia often prolongs bleeding. TEG is a viscoelastic assessment of clot kinetics, and Hct is the main determinant of whole blood viscosity. TEG changes in anemia may be an in vitro artifact due to Hct effect on blood viscosity rather than true in vivo changes in hemostasis. The effect of changes in whole blood viscosity on TEG independent of Hct is not well understood. Study Design and Methods Twenty‐one blood samples from seven dogs were manipulated to produce one of three Hct conditions (45, 20, and 10%). Each was tested in two situations: viscosity adjusted to normal by adding alginate (ALG) or dilution with equal volume of saline (SAL). Both samples were analyzed with TEG simultaneously. Results Twenty percent Hct plus ALG and 10% Hct plus ALG were significantly more viscous than their SAL counterparts (p = 0.0156). Ten percent Hct plus SAL, 20% Hct plus SAL, and 45% Hct plus SAL all had different viscosities (p = 0.006). Twenty percent Hct plus SAL and 10% Hct plus SAL had significantly shorter K and higher angle, MA, and G compared to their ALG counterparts as well as 45% Hct plus SAL (p < 0.05). Conclusions ALG samples with low Hct, normal viscosity showed hypocoagulable tracings, whereas SAL samples with low Hct, low viscosity showed hypercoagulable tracings. TEG variables are influenced by whole blood viscosity altered with ALG, independently of Hct.